2012
DOI: 10.1021/ja210475a
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Theory of Hydrogen Bonding Contribution to Isosteric DNA Base Pairs

Abstract: We address the recent debate surrounding the ability of 2,4-difluorotoluene (F), a low-polarity mimic of thymine (T), to form a hydrogen-bonded complex with adenine in DNA. The hydrogen bonding ability of F has been characterized as small to zero in various experimental studies, and moderate to small in computational studies. However, recent X-ray crystallographic studies of difluorotoluene in DNA/RNA have indicated, based on interatomic distances, possible hydrogen bonding interactions between F and natural b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 60 publications
0
42
1
1
Order By: Relevance
“…Mismatched base pairs contain a consistently lower number of hydrogen bonds than their matched counterparts. Because hydrogen bonding between opposing bases determines DNA stability, (35)(36)(37)(38)(39)(40) these results indicate decreased stability in the presence of mismatches; a result well-known experimentally. (41-44)…”
Section: Hydrogen Bondingmentioning
confidence: 89%
“…Mismatched base pairs contain a consistently lower number of hydrogen bonds than their matched counterparts. Because hydrogen bonding between opposing bases determines DNA stability, (35)(36)(37)(38)(39)(40) these results indicate decreased stability in the presence of mismatches; a result well-known experimentally. (41-44)…”
Section: Hydrogen Bondingmentioning
confidence: 89%
“…Nonpolar thymidine analogues were synthesized to mimic the shape of thymine nucleoside with overall 1.0 Å increment in size from the smallest dH to the largest dI (Figure 5a) (Kim et al, 2005; Kim and Kool, 2005). This system allows us to measure the effects of the loss of hydrogen bonding at the individual “checkpoint” steps (Khakshoor et al, 2012). In addition, the size effect of the template nucleobase can be evaluated by comparing among the five analogues.…”
Section: A Combined Approach To Understand the Molecular Basis Of mentioning
confidence: 99%
“…[3c,d, 4] Backbone C À H···O hydrogen bonds have received less attention, although they have been proposed to play a role in the stabilization of four stranded i-motif structures, [5] and in tight packing of RNA and DNA elements. [8] The prevalence of 2'-fluorinated oligonucleotides in nucleic acids research motivated us to examine the role of enhanced nonconventional hydrogen bonding in duplex stability. Fluorine substitutions are particularly relevant, since fluorine provokes significant charge polarization effects in geminal and vicinal protons, an effect that has been well-characterized in small molecular systems.…”
mentioning
confidence: 99%
“…[7] Recently, Kakshoor et al have observed fluorineenhanced aromatic C À H···N interactions that significantly affect the strength of 2,4-difluorotoluene-adenine base pairs. [8] The prevalence of 2'-fluorinated oligonucleotides in nucleic acids research motivated us to examine the role of enhanced nonconventional hydrogen bonding in duplex stability.…”
mentioning
confidence: 99%